INFRARED SPECTROSCOPIC ANALYSIS OF THE PURIFICATION OF SUNFLOWER OIL FROM WAXY SUBSTANCES USING PERLITE AND VERMICULITE - Usmonova, Zulfiya; Abdurahimov, Ahror; Abdullayeva, Feruza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article investigates the effectiveness of perlite as a filtering agent for the removal of waxy substances from sunflower oil during the winterization process. Sunflower oil tends to become cloudy at low temperatures due to the presence of wax esters, phosphatides, and other wax-like compounds, which negatively affect its appearance and commercial value. In the experimental procedure, the oil was cooled to 7–8 °C to initiate wax crystallization and then filtered through perlite. The filtration efficiency was evaluated using infrared (IR) spectroscopy, which allowed for the identification of functional groups associated with waxy substances. The study also examined the regeneration potential of perlite by subjecting the used filter material to thermal treatment and reusing it in repeated cycles. Physicochemical properties such as porosity and structural stability were also assessed. The IR spectra confirmed that regenerated perlite retained its filtering capabilities. Overall, the results show that perlite is an effective and reusable natural adsorbent for improving the clarity and quality of sunflower oil.